An experiment-based model of condensate throttling and its utilization in load control of 1000 MW power units. (15th August 2017) - Long, Dongteng; Wang, Wei; Yao, Chu; Liu, Jizhen
Abstract: Coal-fired power units are important to stabilize the grid fluctuation especially for the electrical power system with a large proportion of renewable sources. The unit load change speed and range controlled by traditional coordinate control system has become more and more insatiable for the integrations of fluctuant power sources. Condensate throttling is an efficient way to utilize storage energy of units, the mechanism analysis of regulating range and regulation maximum period in wide range of operating condition is proposed, and dynamic model in varying operation conditions is established through lots of trial experiments in a 1000 MW coal-fired power plant, the parameters of model are also discussed in different operating situations. A novel coordinate control system combining traditional coordinate control and condensate throttling system is proposed and the control performance in different regulating rates is investigated, the results and load distribution analysis proved that novel strategy achieve a superior fast response ability and static accuracy. Highlights: Regulation ability is studied in different operating conditions. Dynamic model is investigated using field experiment data. Control system combing condensate throttling and CCS is proposed. A comprehensive indicator is applied to evaluate the fast response ability.